2011
DOI: 10.1186/1471-2350-12-63
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 22 genetic variants with Crohn's Disease risk in the Ashkenazi Jewish population: a case-control study

Abstract: BackgroundCrohn's disease (CD) has the highest prevalence among individuals of Ashkenazi Jewish (AJ) descent compared to non-Jewish Caucasian populations (NJ). We evaluated a set of well-established CD-susceptibility variants to determine if they can explain the increased CD risk in the AJ population.MethodsWe recruited 369 AJ CD patients and 503 AJ controls, genotyped 22 single nucleotide polymorphisms (SNPs) at or near 10 CD-associated genes, NOD2, IL23R, IRGM, ATG16L1, PTGER4, NKX2-3, IL12B, PTPN2, TNFSF15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 46 publications
(76 reference statements)
2
38
0
Order By: Relevance
“…In accordance with our results, the SNP rs1000113 has been associated with Crohn's disease in both German and Ashkenazi Jewish populations [31], [32]. Consistent with our finding where the OR for Crohn's disease association with the minor T allele of rs1000113 was 1.46, a previous study in an Italian population of IBD patients indicated rs1000113 as a CD susceptibility locus with OR of 1.62 (Confidence interval 1.29–2.03) [28].…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our results, the SNP rs1000113 has been associated with Crohn's disease in both German and Ashkenazi Jewish populations [31], [32]. Consistent with our finding where the OR for Crohn's disease association with the minor T allele of rs1000113 was 1.46, a previous study in an Italian population of IBD patients indicated rs1000113 as a CD susceptibility locus with OR of 1.62 (Confidence interval 1.29–2.03) [28].…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, IRGM may particularly affect the onset, severity, and relapse of CD (Lapaquette et al, 2010). Several SNPs in the IRGM gene such as rs13361189 (C>T), rs10065172 (C>T), and rs4958847 (A>G) have been investigated previously (Waterman et al, 2011;Peter et al, 2011;Moon et al, 2013). Previous studies have shown that these 3 polymorphisms may impact the normal expression of the IRGM gene, thus contributing to the susceptibility to CD (Palomino-Morales et al, 2009;Glas et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The top association signals were then replicated in an independent cohort of 589 CD cases and 1,019 controls, recruited throughout North America, Europe, and Israel. Disease diagnosis was confirmed using standard criteria as described elsewhere and full Ashkenazi Jewish ancestry was validated using principal components analysis (11, 44). Our second stage genetic association analysis included a total of 8,619 independent Ashkenazi Jewish and 16,401 independent non-Jewish participants comprising CD cases, PD cases, and healthy controls, genotyped in previous studies (45, 46).…”
Section: Methodsmentioning
confidence: 99%